Geomorphological sketch map of the Evans Cove area (Victoria Land, Antarctica) - SALVATORE, MARIA CRISTINA; BARONI, CARLO; BONDESAN A; MENEGHEL M; OROMBELLI G. (1997)
The morphology of the coastal region between Inexpressible Island and Adélie Cove is here described and mapped. The preliminary geomorphological sketch map in this paper enlarges the southern part of the Northern Foothills that have been previously covered by a published large-scale geomorphological map (Baroni, 1989). The main aim is to produce a geomorphological map at 1:50,000 scale of the whole of the Foothills, from Inexpressible Island to Campbell Glacier. It is part of a cartographic project of the ltalian Programme for Antarctic Research to bring out a series of geomorphological sheets at 1:250,000 scale of Victoria Land. The cartographic base is adopted from a Spot satellite image. The Gps geodetic measurements performed in 1993 (lO points) provided the geometrie control for georeferencing. In this paper the map is reduced to approximately 1:70,000 scale, is reproduced in black and white, and the features mapped are simplified and generalized. In the Terra Nova Bay area the morphology is moulded apparent!y by glaciers up to an altitude of about 1000 m above present sea level. The morphology shows rounded summits with deeply weathered rocks. Above that altitude an alpine type rugged morphology of horns and aretes is present. The glacial deposits were divided into Y ounger Drllt (Denton & Hughes, 1981), here informally named Terra Nova Drift, and Older Drift (Orombelli & alii, 1991). Terra Nova Drift is of Late Wisconsin age and is correlated with the Ross Sea Ice Drift of the Dry Valleys. lt was deposited by glaciers thicker than the present ones that formed an ice sheet whieh was probably linked with the advanced Ross Ice Shelf (Denton & alii, 1989). In the Northern Foothills the Terra Nova Drift can be found up to an altitude of 350-400 m (Baroni & Orombelli, 1987). The legend includes areaI and linear symbols: the former represent rock outcrops and lithological and glacial coverage, the latter epiglacial and geomorphological features. Geomorphological symbols are grouped according to ...